UI/UX Design of Sampah Kita Application Using Design Thinking for Circular Waste Management - Gadi, Kgs Rahmad Bagas; Trinata, Cakra; Hartati, Besse (Department of Informatics Universitas Islam Indonesia, 2026)
Waste management remains a major urban and environmental problem in Indonesia. Low waste sorting behavior, limited segregated collection, and weak user motivation reduce the effectiveness of waste management at the source. This study aims to design the Sampah Kita mobile application as a digital platform for scheduled waste pickup, environmental education, eco-challenges, rewards, and contribution monitoring. The research used the Design Thinking method through empathize, define, ideate, prototype, and test stages. User needs were collected through interviews and a small survey involving housewives, students, and sanitation workers. The findings show that users need practical pickup access, simple guidance, reward-based motivation, and transparent information about their environmental contribution. A high-fidelity prototype was developed and evaluated using the System Usability Scale with twenty respondents. The application obtained an average SUS score of 82, which indicates very good usability. The result suggests that Sampah Kita has potential to support sustainable waste management and circular economy practices through user-centered mobile interaction.